2019
DOI: 10.1016/j.molcel.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Roles of Tom7 and OMA1 during Mitochondrial Import and Activation of PINK1

Abstract: Highlights d Without Tom7, PINK1 is imported into depolarized mitochondria d Negatively charged motif in PINK1 is required for PINK1 import arrest d OMA1 degrades PINK1 that fails to accumulate on depolarized mitochondria d OMA1 deletion rescues Parkin recruitment for some PD-related PINK1 mutants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(166 citation statements)
references
References 56 publications
8
156
2
Order By: Relevance
“…Subsequent actin cloud disassembly might then allow OMA-1 to mediate IMM rearrangement. While OPA1 is likely to be the relevant OMA-1 substrate in these rearrangements, other OMA-1 substrates have been identified as well, including PINK1 (Sekine et al, 2019); C11orf83 (Desmurs et al, 2015) and even OMA-1 itself (Zhang et al, 2014). Reciprocal communication from and to the mitochondrial matrix, through actin polymerization, could serve as another form of interaction between the mitochondrion and its cellular environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent actin cloud disassembly might then allow OMA-1 to mediate IMM rearrangement. While OPA1 is likely to be the relevant OMA-1 substrate in these rearrangements, other OMA-1 substrates have been identified as well, including PINK1 (Sekine et al, 2019); C11orf83 (Desmurs et al, 2015) and even OMA-1 itself (Zhang et al, 2014). Reciprocal communication from and to the mitochondrial matrix, through actin polymerization, could serve as another form of interaction between the mitochondrion and its cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…We next examined the actin assembly factors required for ionomycin-and CCCP-induced actin polymerization. Past results have shown that ionomycin-induced actin polymerization requires the formin INF2 (Chakrabarti et al, 2018;Ji et al, 2015;Shao et al, 2015;Wales et al, 2016).…”
Section: Distinct Actin Polymerization Mechanisms Induced By Mitochonmentioning
confidence: 99%
“…Subsequent actin cloud disassembly might then allow OMA1 to mediate IMM rearrangement. Although OPA1 is likely to be the relevant OMA1 substrate in these rearrangements, other OMA1 substrates have also been identified, including PINK1 (Sekine et al, 2019), C11orf83 (Desmurs et al, 2015) and even OMA1 itself (Zhang et al, 2014). Reciprocal communication from and to the mitochondrial matrix, through actin polymerization, could serve as another form of interaction between the mitochondrion and its cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of the HEK293 C2/C10 DKO cell line was described previously (Huang et al, 2018). HeLa PARL KO, HeLa OMA1 KO , HeLa OMA1 KO stably expressing OMA1 WT or OMA1 E328Q and matched HeLa WT cell lines were a kind from Richard Youle (NIH) and have been described previously (Sekine et al, 2019). HeLa YME1 KO and matched HeLa WT cell lines were a kind gift from Thomas Langer (Cologne) and have been described previously (Hartmann et al, 2016).…”
Section: Cell Culturementioning
confidence: 99%